Exploration of the Integration of Reading and Writing in Narrative Writing Instruction for Junior High School English - Luo, Xinhong; Fan, iaolan; Song, Zengyun; Yang, Jun (Pacific International Journal, 2024)
Under the guidance of the new curriculum standards and in line with the requirements of English subject core literacy, this instructional practice aimed to explore the feasibility, effectiveness, and transferability of integrating reading and writing in narrative writing instruction for junior high school students. Through a one-semester teaching experiment, the study yielded the following findings: 1) Compared to the control group, the experimental group demonstrated significant differences in overall writing achievement, writing content, and the organization of writing structure; 2) The integration of reading and writing in narrative writing instruction positively influenced students’ interest in writing and their confidence in the writing process. Finally, this paper discusses the potential transferability of the reading and writing integration instructional model to writing instruction in the Kashgar region, as well as reflections on the teaching experiment.